2014
DOI: 10.1111/pce.12255
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis reveals the potential metabolites and pathogenesis involved in mulberry yellow dwarf disease

Abstract: To analyse the molecular mechanisms of phytoplasma pathogenicity, the comprehensive metabolomic changes of mulberry leaf and phloem sap in response to phytoplasma infection were examined using gas chromatography-mass spectrometry. The metabolic profiles obtained revealed that the metabolite compositions of leaf and phloem sap were different, and phytoplasma infection has a greater impact on the metabolome of phloem sap than of leaf. Phytoplasma infection brought about the content changes in various metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
47
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 79 publications
(135 reference statements)
9
47
1
2
Order By: Relevance
“…Most of these researches have indicated that photosynthesis is arrested in PaWBinfected seedlings, which is similar to what was reported in other phytoplasma-infected plants [58,59]. In our previous transcriptome research, we identified genes that were differentially expressed in photosystem I and photosystem II, and were associated with decreased photosynthesis [18,19,55].…”
Section: A Mir156-mir160-mir5368 Cluster Regulates Leaf Yellowing In supporting
confidence: 78%
See 1 more Smart Citation
“…Most of these researches have indicated that photosynthesis is arrested in PaWBinfected seedlings, which is similar to what was reported in other phytoplasma-infected plants [58,59]. In our previous transcriptome research, we identified genes that were differentially expressed in photosystem I and photosystem II, and were associated with decreased photosynthesis [18,19,55].…”
Section: A Mir156-mir160-mir5368 Cluster Regulates Leaf Yellowing In supporting
confidence: 78%
“…Changes in plant architecture, such as dwarfism, have been observed in many plants and are mostly caused by hormonal imbalances [58,68]. MiRNAs play important roles in hormone medicated morphology development [69].…”
Section: A Mir160-mir172-mir397 Cluster Regulates Leaf Dwarf Morpholomentioning
confidence: 99%
“…As a consequence, N metabolism in the shoot dictates the rate of NO 3 uptake [1]. The concentration of the majority of the amino acids in phloem exudates is proportional to the concentration in the leaves [7], if no pathogens are involved [8].…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of the majority of the amino acids in phloem exudates is proportional to the concentration in the leaves [7], if no pathogens are involved [8]. Grain filling is mainly dependent on remobilisation from the flag leaf and the adjacent leaf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation